Effect of initial Co content on the microstructure, mechanical properties and high-temperature oxidation resistance of WCoB-TiC ceramic composites. Issue 1 (January 2018) - Ke, Deqing; Pan, Yingjun; Wu, Run; Xu, Yuanyuan; Wang, Pan; Wu, Teng
Abstract: WCoB-TiC ceramic composites with various initial Co content (varying between 10 wt% and 47 wt%) were fabricated by liquid phase reaction sintering (LPRS) in a vacuum furnace. The microstructure, hardness, transverse rupture strength (TRS) and high-temperature oxidation resistance of WCoB-TiC ceramic composites were investigated. The results revealed that initial Co content had an important influence on phase composition of sintered specimens. When the initial Co content was low, the hard phases in WCoB-TiC ceramic composites were W2 CoB2 and TiC. However, when initial Co content was at or higher than 19.6 wt%, W2 CoB2 hard phase changed to WCoB, and CoB changed to Co2 B. With the increase of initial Co content, the hardness and TRS of WCoB-TiC ceramic composites increased firstly and then decreased. WCoB-TiC ceramic composites with an initial Co content of 18.2 wt% showed the highest hardness of 91.6 HRA, and WCoB-TiC ceramic composites with an initial Co content of 19.6 wt% showed the highest TRS of 1783 MPa. Mass gain followed parabolic oxidation kinetics, and the mass gain increased dramatically when initial Co content exceeded 19.6 wt%.